Does the Concept of Cryptotype Support the Systematizing of the Polish Language? - Rudziński, Grzegorz (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
B.L. Whorf created the concept of cryptotype by learning Indian languages and used it to describe English. Experiences in teaching foreigners of Polish as a foreign language indicate the possibility of using the term also in the description of our language. In the adverbial phrase of the place it is possible to distribute the locative forms with the preposition in (w) or with the preposition on (na). This suggests the possibility of dividing the nouns forming this part of the sentence into open nouns, connecting with on and closed nouns, connecting with in. Convincing foreigners about the existence in Polish of a cryptotype of open nouns and the closed nouns’ cryptotype helps them to use these prepositions correctly. Classifying nouns to cryptotypes makes it easier to understand the polysemy of words. The existence of closed cryptotype is easier to demonstrate due to the higher frequency of the preposition in.